KONSEP HIKMAT AL-TASYRÎ’ SEBAGAI ASAS EKONOMI DAN KEUANGAN BISNIS ISLAM MENURUT ALI AHMAD AL-JURJAWI (1866-1961M) DALAM KITAB HIKMAT AL-TASYRÎ’ WA FALSAFATUHU - Sudirman M Johan; Nur Hadi; Akhmad Mujahidin; Ahmad Rofiq; Mawardi Muhammad Shale (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Ali Ahmad Al-Jurjawi (1866-1961) a modernist from the Egyptian city of Jarja. Al-Jurjawi lived in a time of shock, known as the Egyptian revolution from the clutches of France. European colonization of the Islamic world (Egypt), which tends to manage the economy with a conventional (secular) system. These conditions affect the construction of scholarship which is occupied by Al-Jurjawi, plus the difficulty of finding the ideal books, especially regarding Islamic law and wisdom or secrets that exist in Islamic teachings. Starting from such a situation Al-Jurjawi much got the idea of philosophy and thought and determined to write a book that discusses the wisdom of Islamic Shari'ah, which is named Hikmat al-Tasyrî 'wa Falsafatuhu. Then how kosep wisdom al-Tashrî 'became the economic and financial principles of Islamic business according to Al-Jurjawi in the book. The result, the concept of wisdom al-Tasyrî 'Al-Jurjawi is amazing wisdom, astonishing mind and satisfy the heart of the shari'ah of the divine religion aims to know God, inhumanizing, knowing how to worship and Think about it by establishing the law necessary to be done amar ma'ruf nahi mungkar and benefit servants of the world and the hereafter. The reason for wisdom of al-Tashrî 'as the economic and financial principle in Islamic business according to Al-Jurjawi, to realize submission to the Shari'ah of Allah; preserving the Sunnah of the Prophet; keep away from the forbidden; foster moral development; realizing brotherhood and unity. All according to Al-Jurjawi contains benefit the world and the hereafter, in an effort to know God by worshiping and ma'ruf nahi munkar and morally noble character. It is embodied in the concept of hablum minnallâh wa minannâs. Benefit as the principle of innovation of economic and financial activities in contemporary Islamic business according to the researchers lies in the wisdom of ihyâu al-Mawât his Al-Jurjawi is to innovate in business for benefit people